Nitrogen use efficiency, water saving and yield of rice transplanting on raised bed over traditional flat method. (7th February 2017) - Majeed, Abdul; Niaz, Abid; Muhmood, Atif; Ahmad, Zahid Ashfaq; Ilyas, Muhammad; Wakeel, Abdul
ABSTRACT: Flat transplanting with flooded irrigation is commonly used for growing rice, but it results in ineffective use of applied fertilizer and water. The objective of this study was to compare nitrogen use efficiency and water saving of rice transplanted on beds and on flat ground. This field experiment was performed in randomized complete design for three continuous years and all treatments were repeated three times. Results showed that transplanting of four lines of rice nursery on bed and one line in furrow and nitrogen application at 150 kg ha −1 recorded 16.06, 21.81, 16.0 and 20.21% higher paddy yield, nitrogen (N) uptake in paddy, N use efficiency and N agronomic efficiency than traditional flat method at same N level. Without loss in yield, about 25 kg ha −1 of N fertilizer and 24% of water can be saved with bed transplanting of rice as compared to flat method.